Notch dimerization provides robustness against environmental insults and is required for vascular integrity - Kristina Preusse; Kim Cochran; Quanhui Dai; Raphael Kopan (PLoS ONE, 2025)
The Notch intracellular domain (NICD) regulates gene expression during development and homeostasis in a transcription factor complex that binds DNA either as monomer, or cooperatively as dimers. Mice expressing N otch d imerization- d eficient (NDD) alleles of Notch1 and Notch2 have defects in multiple tissues that are sensitized to environmental insults. Here, we report that cardiac phenotypes and DSS (Dextran Sodium Sulfate) sensitivity in NDD mice can be ameliorated by housing mice under hypo-allergenic conditions (food/bedding). However, compound heterozygote NDD mice (N1 RA/– ; N2 RA/– ) in hypo-allergenic conditions subsequently develop severe hydrocephalus and hemorrhages. Further analysis revealed multiple vascular phenotypes in NDD mice including leakage, malformations of brain vasculature, and vasodilation in kidneys, leading to demise around P21. This mouse model is thus a hypomorphic allele useful to analyze vascular phenotypes and gene-environment interactions. The possibility of a non-canonical Notch signal regulating barrier formation in the gut, skin, and blood systems is discussed.